COMPARATIVE GEOLOGICAL AND ECONOMIC ASSESSMENT OF THE TITANIUM DEPOSITS OF UKRAINE USING THE EXAMPLE OF THE NOVOMYRHOROD PLACERS DISTRICT - OKHOLINA, Tetiana; KUZMANENKO, Halyna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article considers one of the methods of geological and economic assessment – ranking of titanium ore deposits on a point scale on the example of the Novomyrhorod placer district, which includes the Birzulivske deposit, Likarivske, Andriivske, Valuivske, Novomyrhorod placers, as well as the Eastern and Western residual areas. A brief geological description of the compared titanium objects is given, as well as the geological, qualitative and economic indicators are used to make a comparative geological and economic assessment of the studied deposits and placers. The use of a scoring scale allows comparing objects with different degrees of exploration and can be used to determine the prospects of any deposit among a number of objects with a limited amount of information.